Entertainment services with special reference to music, mas, and the film and video segments - Demas, Allison (CRNM Christ ChurchBB, 2001)
Deals with the trade related issues that impact on the entertainment industry in the English-speaking Caribbean. Makes proposals regarding the negotiating strategy to be adopted by the Commonwealth Caribbean.